Secondary battery and electric device

By using linear adhesive and dot-like adhesive in the negative electrode film layer, the problem of short service life of the secondary battery is solved, and higher cycle stability and kinetic performance are achieved.

CN119852531APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311675385.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The service life of existing secondary batteries is relatively short, which affects the battery life of the power consumption device.

Method used

Linear adhesive and dot-like adhesive are used in the partition in the negative electrode film layer. By adjusting the distribution area and mass proportion of the adhesive, the cohesion force of the negative electrode film layer and the adhesion force to the current collector are improved.

Benefits of technology

It effectively reduces the moisture absorption and expansion rate of the electrode plate, improves the cycle stability and dynamic performance of the battery, and extends the service life of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852531A_ABST
    Figure CN119852531A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and an electric device. The secondary battery comprises a negative electrode piece, the negative electrode piece comprises a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, the negative electrode film layer is provided with a first surface far away from the negative electrode current collector and a second surface opposite to the first surface, the thickness of the negative electrode film layer is marked as H, the area from the second surface of the negative electrode film layer to the thickness range of 0.3 H is marked as the first area of the negative electrode film layer, the area from the first surface of the negative electrode film layer to the thickness range of 0.3 H is marked as the second area of the negative electrode film layer, the first area comprises a first binder, and the first binder is a linear binder; the second area comprises a second binder, and the second binder is a dotted binder. According to the secondary battery, the cold pressing rebound rate and the cyclic expansion rate of the pole piece can be reduced, and the cycle stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a secondary battery and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.

[0003] As the application scope of secondary batteries becomes wider and wider, people have put forward higher requirements on the performance of secondary batteries, such as requiring the service life of secondary batteries to be continuously improved to increase the endurance of electrical devices. Summary of the invention

[0004] The present application is developed in view of the above-mentioned technical problems, and its purpose is to provide a secondary battery and an electrical device to increase the service life of the secondary battery.

[0005] In a first aspect, the present application provides a secondary battery, comprising a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, the negative electrode film layer having a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is denoted as H, the area within a thickness range from the second surface of the negative electrode film layer to 0.3H is denoted as the first area of ​​the negative electrode film layer, the area within a thickness range from the first surface of the negative electrode film layer to 0.3H is denoted as the second area of ​​the negative electrode film layer, the first area comprises a first binder, and the first binder is a linear binder; the second area comprises a second binder, and the second binder is a point binder.

[0006] By using a linear first binder in the first area of ​​the negative electrode film layer close to the current collector side and using a dot-shaped second binder in the second area of ​​the negative electrode film layer away from the current collector side, the probability of the linear binder contacting with moisture can be effectively reduced, the moisture absorption rate of the negative electrode pole piece can be reduced, and the increase in pole piece thickness caused by the moisture absorption of the linear binder can be alleviated. The linear binder can give full play to its multiple polar functional groups and strong bonding force, thereby achieving a low expansion rate of the pole piece and reducing the probability of a significant deterioration in the defective rate and battery cycle stability.

[0007] In any embodiment of the present application, the weight average molecular weight of the first binder is greater than the weight average molecular weight of the second binder.

[0008] The linear first binder has a higher weight-average molecular weight than the dot-shaped second binder, which is beneficial to improving the cohesion of the negative electrode film layer and the bonding force between the negative electrode film layer and the current collector, further reducing the rebound rate of the electrode after cold pressing and the expansion rate of the battery after full charge, and comprehensively improving the processing performance and cycle stability of the battery.

[0009] In any embodiment of the present application, the mass proportion of the first binder in the first region is greater than the mass proportion of the second binder in the second region; the mass proportion of the first binder in the first region refers to the mass percentage of the first binder based on the total mass of the negative electrode film layer in the first region; the mass proportion of the second binder in the second region refers to the mass percentage of the second binder based on the total mass of the negative electrode film layer in the second region.

[0010] During the drying process of the electrode slurry coating, the binder near the current collector side tends to float to the surface of the negative electrode film layer as the solvent evaporates, that is, it tends to migrate from the first area of ​​the electrode to the second area of ​​the electrode, resulting in insufficient binder content in the first area of ​​the electrode, and significantly deteriorating the cohesion of the negative electrode film layer and the adhesion between the negative electrode film layer and the current collector; at the same time, the floating binder tends to block the pore structure in the second area of ​​the upper layer of the electrode, causing difficulty in electrolyte infiltration, and then leading to the problem of insufficient battery dynamics. Setting the mass proportion of the first binder in the first area to be greater than the mass proportion of the second binder in the second area, on the one hand, helps to improve the cohesion of the negative electrode film layer and the adhesion between the negative electrode film layer and the current collector, restrain the expansion of the negative electrode active material, and improve the battery cycle stability; on the other hand, it can reduce the pore blockage on the surface of the electrode and optimize the dynamic performance of the battery.

[0011] In any embodiment of the present application, the first binder includes an acrylic binder; and / or the second binder includes polystyrene butadiene copolymer.

[0012] In any embodiment of the present application, the acrylic binder includes at least one of polyacrylic acid, polymethacrylic acid, polymethyl acrylate, polyethyl methacrylate, polyhydroxyethyl methacrylate, polyhydroxyethyl acrylate, polyhydroxypropyl acrylate, polyhydroxypropyl methacrylate, polyhydroxyethyl acrylate, polypropyl methacrylate, polyethyl acrylate, and polymethyl methacrylate.

[0013] Acrylic binders have more polar functional groups and are linear binders. They can fully stretch in the solvent and coat the surface of the negative electrode active material, with which they have a large contact area. They can effectively reduce the rebound of the electrode and improve the cycle stability of the battery through bonding.

[0014] In any embodiment of the present application, the weight average molecular weight of the first binder is 500-1500, and can be 800-1000; the weight average molecular weight of the second binder is 100-200.

[0015] In any embodiment of the present application, the mass proportion of the first binder in the first region is 1.0% to 3.0%, optionally 1.0% to 2.5%, and / or the mass proportion of the second binder in the second region is 0.6% to 1.5%, optionally 0.6% to 1.2%.

[0016] The binder within the above content range enables the battery to have both good cycle stability and kinetic performance.

[0017] In any embodiment of the present application, the compaction density of the negative electrode film layer is 1.55 g / cm 3 -1.68g / cm 3 .

[0018] In any embodiment of the present application, the negative electrode film layer includes a conductive agent, and based on the total mass of the negative electrode film layer, the mass proportion of the conductive agent is 0.4%-2.0%.

[0019] In any embodiment of the present application, the first region and / or the second region comprises graphite, and the specific surface area of ​​the graphite is 1.2 m 2 / g-1.8m 2 / g, optional 1.25m 2 / g-1.70m 2 / g.

[0020] The specific surface area of ​​the graphite material within the above range is helpful to further reduce the degree of side reactions of the graphite material and improve the cycle life of the secondary battery.

[0021] In any embodiment of the present application, the volume distribution particle size Dv50 of the graphite is 7.0 μm-14.0 μm, and can be optionally 9.0 μm-12.0 μm.

[0022] In any embodiment of the present application, the particle size distribution of the graphite (Dv90-Dv10) / Dv50 is 1.10-1.60, and can be optionally 1.20-1.50.

[0023] Controlling the particle size distribution of graphite materials within the above range is conducive to improving the compaction of graphite materials and increasing the compaction density of negative electrode sheets. In other words, the cold pressing pressure required for the negative electrode sheets to achieve the same compaction density is smaller, thereby reducing the probability of cracking of the graphite material during the cold pressing process, and further improving the integrity of the graphite material during processing; and the small stress inside the graphite material particles is conducive to maintaining the long-period pore structure of the electrode sheet during the cycle process, and the original pore structure of the electrode sheet can be maintained during the cycle process, so that the lithium ion insertion path remains unobstructed, while reducing the re-filming of the graphite material during the charging process, improving the dynamic performance, cycle life and storage stability. Furthermore, the particle size distribution within the above range can also improve the uniformity of lithium insertion between graphite material particles, reduce polarization, avoid lithium precipitation caused by uneven current density, and help achieve long-term cycle stability. In addition, the particle size distribution within the above range can also help improve the processing performance of the pole piece, and will not affect the uniformity of slurry stirring due to excessive small particles in the graphite material, which is beneficial to improving the uniformity and stability of the pole piece quality and further improving the long-term cycle stability.

[0024] In any embodiment of the present application, the gram capacity of the graphite is 345 mAh / g-355 mAh / g, and can be optionally 347 mAh / g-353 mAh / g.

[0025] During the charge and discharge process, the graphite material with a gram capacity within the above range will not have a significant lattice expansion due to the high graphitization of the graphite material, nor will it be difficult to compact due to the low graphitization of the graphite material, so that a higher cold pressing pressure is required to achieve the required compaction density of the pole piece, which will cause the graphite material to break during the cold pressing process and generate new interfaces during the cycle process to consume too much active lithium. The graphite material with a gram capacity within the above range can comprehensively improve the cycle life of the secondary battery.

[0026] In any embodiment of the present application, the graphite powder compaction density under a pressure of 49000N is less than or equal to 1.85g / cm 3 , optional 1.75g / cm 3 -1.84g / cm 3 .

[0027] Graphite materials with a powder compaction density within the above range can easily maintain high particle integrity during the cold pressing process, which helps to improve the cycle life of secondary batteries.

[0028] In any embodiment of the present application, the graphite particle body includes an internal region and a surface region that at least partially surrounds the internal region, and the surface region refers to a region extending 30 nm from the surface of the particle body to the interior of the particle, and the surface region includes a disordered layer; optionally, the thickness of the disordered layer is 1 nm-20 nm.

[0029] The disordered layer mainly includes amorphous carbon. The carbon atoms in the amorphous carbon structure have no regular arrangement, which makes the interaction between its molecules more complex, resulting in higher strength and hardness than the graphite crystals in the internal area, which reduces the probability of surface damage of graphite particles due to friction between particles and between particles and stirring tanks during slurry preparation, reduces the risk of graphite material particles cracking and exposing new interfaces during the cold pressing of the pole piece, and allows the graphite material to maintain higher particle integrity during the manufacturing process. Graphite materials with high particle integrity have fewer surface defects and a good interface with the electrolyte, which can effectively reduce the side reactions between the negative electrode and the electrolyte, reduce the loss of active lithium, and are beneficial to the improvement of battery storage stability and cycle stability. At the same time, the disordered layer on the graphite material also helps to improve the infiltration of the electrolyte and the negative electrode, and improve the battery kinetic performance.

[0030] Different from the disordered layer coated on the surface of the graphite material in the prior art, the disordered layer of the graphite material provided in the embodiment of the present application is located in the particle body of the graphite material, which is derived from the same raw material as the graphite material and is not prepared by post-processing. Therefore, compared with the graphite material obtained by surface coating treatment to obtain the disordered layer, the graphite material has better material consistency, so that the battery exhibits a longer cycle life, and achieves a balance between battery kinetic performance and cycle stability and storage stability, and is particularly suitable for energy storage batteries with extremely high requirements for cycle life and storage life.

[0031] In any embodiment of the present application, the graphite includes primary particles and secondary particles at the same time; optionally, based on the total number of the primary particles and the secondary particles, the number of the secondary particles accounts for less than or equal to 50%.

[0032] Graphite materials with a low percentage of secondary particles are conducive to maintaining the particle integrity of graphite materials during battery preparation, reducing the generation of new interfaces, reducing the consumption of active lithium during the cycle, and further improving the cycle stability of secondary batteries. At the same time, a certain number of secondary particles can reduce the expansion of the negative electrode while taking into account the dynamic performance of the secondary battery, so that the battery cell has a dynamic window for the entire life cycle, and will not cause lithium precipitation due to uneven current distribution, causing a sharp decline in battery capacity and a sharp deterioration in battery life, thereby comprehensively improving the cycle stability of the battery.

[0033] In any embodiment of the present application, the graphitization degree of the graphite is 92.0%-94.0%.

[0034] In any embodiment of the present application, the graphite material I D / I G is 0.05-0.10, among which I D / I G is the ratio of the D peak intensity to the G peak intensity obtained from the Raman spectrum, I D Indicates that the Raman spectrum is at 1350±100cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±100cm -1 The G peak intensity at .

[0035] Graphite Materials I D / I G It can be used to characterize the surface disorder of graphite materials. Different from the active material with a disordered layer coated on the surface of the graphite particle body, the graphite material provided in the embodiment of the present application has a disordered layer on the surface and has a lower surface disorder. The disordered layer in the active material with a disordered layer coated on the surface of the graphite particle body is usually derived from the coated organic carbon, so that the disordered layer after carbonization has a high surface disorder; while the disordered layer structure in the surface area of ​​the graphite material provided in the embodiment of the present application and the other parts of the graphite material are derived from the same precursor, and the disordered layer has a high uniformity and an extremely thin thickness, so that it can have a lower surface disorder. On the one hand, this enables the graphite material to take advantage of the disordered layer and improve the kinetic performance of the battery, and will not cause too many side reactions due to the excessive disorder of the surface layer of the material, and can take into account the cycle stability of the battery while improving the kinetic performance of the battery.

[0036] A second aspect of the present application provides an electrical device, which includes the secondary battery of the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0038] Figure 1 It is a schematic diagram of one embodiment of the negative electrode plate of the present application.

[0039] Figure 2 It is a schematic diagram of another embodiment of the negative electrode plate of the present application.

[0040] Figure 3 It is a schematic diagram of another embodiment of the negative electrode plate of the present application.

[0041] Figure 4 It is a schematic diagram of a cross-sectional image of a particle of the graphite material of the present application.

[0042] Figure 5 It is a schematic diagram of one embodiment of the secondary battery of the present application.

[0043] Figure 6 It is an exploded schematic diagram of one embodiment of the secondary battery of the present application.

[0044] Figure 7 It is a schematic diagram of an embodiment of a battery module of the present application.

[0045] Figure 8 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0046] Fig. 9 yes Figure 8 An exploded schematic diagram of an embodiment of a battery pack is shown.

[0047] Fig.10 It is a schematic diagram of one embodiment of an electric device including the secondary battery of the present application as a power source.

[0048] Fig.11 This is a scanning electron microscope image of the second region of one embodiment of the negative electrode sheet of the present application.

[0049] Fig.12 This is a scanning electron microscope image of the first region of one embodiment of the negative electrode sheet of the present application.

[0050] In the accompanying drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 secondary battery, 51 shell, 52 electrode assembly, 53 cover plate, 10 negative electrode sheet, 101 negative electrode current collector, 102 negative electrode film layer, 102a first surface, 102b second surface, 1021 first region, 1022 second region, 1023 middle region, 200 graphite material, 201 surface region, 202 internal region. DETAILED DESCRIPTION

[0051] Hereinafter, the embodiments of the secondary battery and the electric device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0052] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0053] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0054] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0055] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0056] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0057] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0058] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.

[0059] If not otherwise specified, the values ​​of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.

[0060] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.

[0061] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0062] Binder is an important component of the secondary battery electrode. Although it occupies a small proportion in the electrode, it has a very close relationship with the electrochemical performance of the secondary battery. The main function of the binder is to bind the various components of the electrode such as active materials, conductive agents, current collectors, etc. together to form a stable electrode structure, and at the same time make the active materials and conductive agents better contact to form a good conductive network; at the same time, the binder can also alleviate the volume expansion and contraction of the positive and negative electrode materials during the process of lithium insertion and extraction, and stabilize the internal structure of the electrode to obtain good cycle performance. Taking the negative electrode binder as an example, during the use of the secondary battery, accompanied by charging and discharging, the extraction / insertion of active ions in the negative electrode active material will cause the volume expansion / contraction of the negative electrode active material, the increase of the interplanar spacing of the negative electrode active material, and the increase of the volume expansion rate. Therefore, it is also required that the negative electrode binder can play a certain buffering role on the expansion / contraction of the negative electrode active material. Styrene-butadiene rubber (SBR) is a commonly used negative electrode binder. It is an elastomer made by copolymerization of 1,3-butadiene and styrene, which can effectively improve the flexibility of the negative electrode. However, the styrene-butadiene rubber is in the form of dots in the negative electrode film layer, and is connected to the negative electrode active materials in a point-bonding manner. The bonding surface is small, and it is difficult to effectively reduce the rebound of the negative electrode plate after cold pressing and the expansion of the negative electrode active materials after full charging, which is not conducive to improving the cycle stability of the secondary battery.

[0063] Based on this, the present application provides a secondary battery, including a negative electrode sheet, Figures 1 to 3 Schematic diagram of the negative electrode sheet of the present application. Figures 1 to 3 As shown, the negative electrode plate 10 includes a negative electrode current collector 101 and a negative electrode film layer 102 formed on at least one surface of the negative electrode current collector 101, the negative electrode film layer 102 has a first surface 102a away from the negative electrode current collector 101 and a second surface 102b arranged opposite to the first surface 102a, the thickness of the negative electrode film layer 102 is recorded as H, the area within the thickness range from the second surface 102b of the negative electrode film layer to 0.3H is recorded as the first area 1021 of the negative electrode film layer, and the area within the thickness range from the first surface 102a of the negative electrode film layer to 0.3H is recorded as the second area 1022 of the negative electrode film layer, the first area 1021 includes a first binder, and the first binder is a linear binder; the second area 1022 includes a second binder, and the second binder is a point binder.

[0064] In the present application, the morphology of the binder can be observed by using a scanning electron microscope to obtain a morphology picture of the sample to be tested. As an example, the negative electrode sheet is cut into a 10mm×5mm sample to be tested, and the sample to be tested is clamped with two copper plates. The sample to be tested and the copper plates are fixed with double-sided tape, and a flat iron block of a certain mass (500g) is used to press for a certain time of 10 minutes to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors and glued to a sample table with conductive glue. The sample slightly protrudes from the edge of the sample table. The morphology of the binder can be observed by using a scanning electron microscope to obtain a surface morphology picture of the sample to be tested.

[0065] Fig.11 is a scanning electron microscope image of a second region of an embodiment of a negative electrode sheet of the present application; Fig.12 FIG. 1 is a scanning electron microscope image of the first region of one embodiment of the negative electrode sheet of the present application. Fig.11 As shown in the figure, the point-shaped binder provides bonding force between the negative electrode active materials in a point contact manner, which cannot effectively cover and protect the surface of the negative electrode active materials, and it is difficult to effectively inhibit the expansion of the negative electrode active materials, resulting in cycle deterioration. Linear binders often have more polar functional groups. During the slurrying process, the polar functional groups interact with the water solvent to enable the binder to fully stretch and coat the surface of the negative electrode active material, such as Fig.12 As shown. The coating of the linear second binder on the surface of the negative electrode active material can fully improve the bonding strength between the negative electrode active materials and between the negative electrode film layer and the negative electrode current collector, which is beneficial to the improvement of the cohesion of the negative electrode plate. However, the polar functional groups in the linear binder are also easy to form strong polar hydrogen bonds with water molecules in the air, resulting in the plate to easily absorb moisture in the air after cold pressing, causing the plate thickness to rebound too much, affecting the processing performance of the battery cell into the shell, and even causing the deterioration of the battery cell cycle stability.

[0066] By using a linear first binder in the first area of ​​the negative electrode film layer close to the current collector side and using a dot-shaped second binder in the second area of ​​the negative electrode film layer away from the current collector side, the probability of the linear binder contacting with moisture can be effectively reduced, the moisture absorption rate of the negative electrode pole piece can be reduced, and the increase in pole piece thickness caused by the moisture absorption of the linear binder can be alleviated. The linear binder can give full play to its multiple polar functional groups and strong bonding force, thereby achieving a low expansion rate of the pole piece and reducing the probability of a significant deterioration in the defective rate and battery cycle stability.

[0067] In some embodiments, the weight average molecular weight of the first binder is greater than the weight average molecular weight of the second binder.

[0068] As used herein, the term "weight average molecular weight" refers to the sum of the products of the weight fractions of molecules with different molecular weights in a polymer and their corresponding molecular weights.

[0069] In the present application, the weight average molecular weight of the binder can be tested by methods known in the art, such as gel chromatography, such as using a Waters 2695Isocratic HPLC gel chromatograph (differential refractive index detector 2141) for testing. A polystyrene solution sample with a mass fraction of 3.0% is used as a reference, and a matching chromatographic column (oily: Styragel HT5DMF7.8*300mm+Styragel HT4) is selected. A 3.0% binder glue solution is prepared with purified N-methylpyrrolidone (NMP) solvent, and the prepared solution is allowed to stand for one day for use. During the test, tetrahydrofuran is first drawn with a syringe, rinsed, and repeated several times. Then 5mL of the experimental solution is drawn, the air in the syringe is removed, and the needle tip is wiped dry. Finally, the sample solution is slowly injected into the injection port. After the indication is stable, data is obtained and the weight average molecular weight is read.

[0070] The linear first binder has a higher weight-average molecular weight than the dot-shaped second binder, which is beneficial to improving the cohesion of the negative electrode film layer and the bonding force between the negative electrode film layer and the current collector, further reducing the rebound rate of the electrode after cold pressing and the expansion rate of the battery after full charge, and comprehensively improving the processing performance and cycle stability of the battery.

[0071] In some embodiments, the mass proportion of the first binder in the first region is greater than the mass proportion of the second binder in the second region; the mass proportion of the first binder in the first region refers to the mass percentage of the first binder based on the total mass of the negative electrode film layer in the first region; the mass proportion of the second binder in the second region refers to the mass percentage of the second binder based on the total mass of the negative electrode film layer in the second region.

[0072] During the drying process of the electrode slurry coating, the binder near the current collector side tends to float to the surface of the negative electrode film layer as the solvent evaporates, that is, it tends to migrate from the first area of ​​the electrode to the second area of ​​the electrode, resulting in insufficient binder content in the first area of ​​the electrode, and significantly deteriorating the cohesion of the negative electrode film layer and the adhesion between the negative electrode film layer and the current collector; at the same time, the floating binder tends to block the pore structure in the second area of ​​the upper layer of the electrode, causing difficulty in electrolyte infiltration, and then leading to the problem of insufficient battery dynamics. Setting the mass proportion of the first binder in the first area to be greater than the mass proportion of the second binder in the second area, on the one hand, helps to improve the cohesion of the negative electrode film layer and the adhesion between the negative electrode film layer and the current collector, restrain the expansion of the negative electrode active material, and improve the battery cycle stability; on the other hand, it can reduce the pore blockage on the surface of the electrode and optimize the dynamic performance of the battery.

[0073] In some embodiments, the first binder comprises an acrylic binder; and / or the second binder comprises polystyrene butadiene copolymer.

[0074] In this article, the acrylic binder refers to a polymer with acrylic monomer as the main polymerization monomer, which can be a homopolymer or a copolymer. The acrylic monomer includes acrylic acid monomer or its derivatives.

[0075] In some embodiments, the acrylic binder includes at least one of polyacrylic acid, polymethacrylic acid, polymethyl acrylate, polyethyl methacrylate, polyhydroxyethyl methacrylate, polyhydroxyethyl acrylate, polyhydroxypropyl acrylate, polyhydroxypropyl methacrylate, polyhydroxyethyl acrylate, polypropyl methacrylate, polypropyl methacrylate, polyethyl acrylate, and polymethyl methacrylate.

[0076] Acrylic binders have more polar functional groups and are linear binders. They can fully stretch in the solvent and coat the surface of the negative electrode active material, with which they have a large contact area. They can effectively reduce the rebound of the electrode and improve the cycle stability of the battery through bonding.

[0077] As used herein, "styrene butadiene copolymer" refers to a polymer obtained by copolymerizing butadiene monomers with styrene monomers.

[0078] In some embodiments, the weight average molecular weight of the first binder is 500-1500, and can be 800-1000; the weight average molecular weight of the second binder is 100-200.

[0079] In some embodiments, the weight average molecular weight of the first binder is 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500 or any range therebetween.

[0080] In some embodiments, the weight average molecular weight of the second binder is 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200 or any range therebetween.

[0081] In some embodiments, the mass proportion of the first binder in the first region is 1.0% to 3.0%, optionally 1.0% to 2.5%, and / or the mass proportion of the second binder in the second region is 0.6% to 1.5%, optionally 0.6% to 1.2%.

[0082] The mass content of the binder in different areas of the negative electrode sheet can be tested by any known method in the art. As an example, take a clean copper foil and lay it flat on the table, cut the negative electrode sheet to be tested into a 20cm×10cm sheet; prepare a clean blade, hold the sheet with your left hand, hold the blade with your right hand, set the blade and the sheet at 45°, select the middle of the sheet and scrape the powder from left to right, the length of the scraping powder is 10cm, and the width is 5cm. If there are 10 times from the beginning of scraping powder to leaking copper foil, the first 3 scraping powders are taken as samples of the second area, and the last 3 scraping powders are taken as samples of the first area, and the collected samples are stored in a sealed bottle. Weigh 50mg of the collected sample, place it in an alumina crucible and shake it flat, use a thermogravimetric analyzer to detect the binder content in the sample (the atmosphere is nitrogen, the flow rate is 20mL / min), and heat the sample from 25℃ to 600℃ at a heating rate of 10℃ / min. The mass percentage of the sample loss in different areas is the mass proportion of the binder in different areas.

[0083] In some embodiments, the mass percentage of the first binder in the first region is 1.0%, 1.3%, 1.6%, 1.9%, 2.2%, 2.5%, 2.7%, 3.0% or any range therebetween.

[0084] In some embodiments, the mass percentage of the second binder in the second region is 0.6%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5% or any range therebetween.

[0085] When the mass proportion of the first binder in the first region is 1.0% to 2.5%, the battery has both good cycle stability and dynamic performance.

[0086] When the mass proportion of the second binder in the second region is 0.6% to 1.2%, the battery has both good cycle stability and dynamic performance.

[0087] In some embodiments, the compaction density of the negative electrode film layer is 1.55 g / cm 3 -1.68g / cm 3 .

[0088] In the present application, the compaction density of the negative electrode film layer can be tested by methods known in the art. As an example, an electronic balance is used to weigh a negative electrode sheet with an area of ​​S, and the weight is recorded as W1, and a micrometer is used to measure the thickness T1 of the negative electrode sheet. Then wipe off the weighed electrode sheet film layer, weigh the weight of the negative electrode current collector, record it as W2, and use a micrometer to measure the thickness T2 of the negative electrode current collector. Then the compaction density of the negative electrode film layer PD = (W1-W2) / [(T1-T2)×S].

[0089] In some embodiments, the compaction density of the negative electrode film layer is 1.55 g / cm 3 , 1.58g / cm 3 , 1.61g / cm 3 , 1.64g / cm 3 、1.68g / cm 3 Or any range of values ​​in between.

[0090] In some embodiments, the negative electrode film layer includes a conductive agent, and based on the total mass of the negative electrode film layer, the mass proportion of the conductive agent is 0.4%-2.0%.

[0091] In some embodiments, based on the total mass of the negative electrode film layer, the mass proportion of the conductive agent is 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4, 1.6%, 1.8%, 2.0% or any numerical range therebetween.

[0092] In some embodiments, the first region and / or the second region comprises graphite. It is understood that the first region / the second region may comprise at least one graphite material, and the first region and the second region may comprise the same or different graphite materials.

[0093] In some embodiments, the specific surface area of ​​the graphite is 1.2 m 2 / g-1.8m 2 / g, optional 1.25m 2 / g-1.70m 2 / g.

[0094] In the present application, the specific surface area of ​​the graphite material can be tested by methods known in the art. As an example, referring to GB / T 19587-2017, the specific surface area analysis test method of nitrogen adsorption is used for testing, and the specific surface area is calculated by the BET (BrunauerEmmett Teller) method. The testing instrument can be the Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.

[0095] In some embodiments, the specific surface area of ​​the graphite is 1.2 m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g or any range of values ​​between them.

[0096] The low specific surface area of ​​graphite materials helps to further reduce the degree of side reactions of graphite materials and improve the cycle life of secondary batteries.

[0097] In some embodiments, the volume distribution particle size Dv50 of the graphite is 7.0 μm-14.0 μm, and can be optionally 9.0 μm-12.0 μm.

[0098] As used herein, the term "volume distribution particle size Dv50" refers to the particle size corresponding to when the cumulative volume distribution number of particles reaches 50% in the particle size distribution curve.

[0099] In the present application, the volume distribution particle size Dv50 of the graphite material can be tested by a method known in the art. As an example, referring to GB / T 19077-2016, it is measured by a laser particle size analyzer. The testing instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0100] In some embodiments, the volume distribution particle size Dv50 of the graphite is 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, or any range therebetween.

[0101] In some embodiments, the particle size distribution of the graphite is (Dv90-Dv10) / Dv50 of 1.10-1.60, and optionally 1.20-1.50.

[0102] In this article, the terms "Dv90" and "Dv10" refer to the particle sizes corresponding to when the cumulative volume distribution number of particles reaches 90% and 10% in the particle size distribution curve, respectively.

[0103] In the present application, the volume distribution particle size Dv90 and Dv10 of the graphite material can be tested by methods known in the art. As an example, referring to GB / T 19077-2016, a laser particle size analyzer is used for determination. The testing instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0104] In some embodiments, the particle size distribution of the graphite (Dv90-Dv10) / Dv50 is 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.50, 1.60 or any range therebetween.

[0105] Controlling the particle size distribution of graphite materials within the above range is conducive to improving the compaction of graphite materials and increasing the compaction density of negative electrode sheets. In other words, the cold pressing pressure required for the negative electrode sheets to achieve the same compaction density is smaller, thereby reducing the probability of cracking of the graphite material during the cold pressing process, and further improving the integrity of the graphite material during processing; and the small stress inside the graphite material particles is conducive to maintaining the long-period pore structure of the electrode sheet during the cycle process, and the original pore structure of the electrode sheet can be maintained during the cycle process, so that the lithium ion insertion path remains unobstructed, while reducing the re-filming of the graphite material during the charging process, improving the dynamic performance, cycle life and storage stability. Furthermore, the particle size distribution within the above range can also improve the uniformity of lithium insertion between graphite material particles, reduce polarization, avoid lithium precipitation caused by uneven current density, and help achieve long-term cycle stability. In addition, the particle size distribution within the above range can also help improve the processing performance of the electrode, and will not affect the uniformity of slurry stirring due to excessive small particles in the graphite material, which is beneficial to improving the uniformity and stability of the electrode quality and helping to achieve long-cycle stability.

[0106] In some embodiments, the gram capacity of the graphite is 345 mAh / g-355 mAh / g, and can be optionally 347 mAh / g-353 mAh / g.

[0107] As used herein, the term "gram capacity" refers to the ratio of the amount of electricity that an active material can release to the mass of the active material.

[0108] In the present application, the gram capacity of graphite can be tested by methods known in the art. As an example, the graphite sample is mixed with the conductive agent carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 91.6:1.8:6.6 in an appropriate amount of solvent NMP and stirred to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode and the polypropylene (PP) film is used as the isolation membrane, and the CR2430 button battery is assembled in an argon-protected glove box, wherein the electrolyte given in the embodiment of the present application is used. At 25°C, the button battery prepared above is first discharged to 0.005V at a constant current of 0.05C, and then discharged to 0.005V at a constant current of 10μA, and left to stand for 5min, and the first cycle discharge capacity of the button battery is recorded; then, it is charged to 2.0V at a constant current of 0.1C, and the charging capacity of the button battery is recorded. The ratio of the charging capacity of the button cell to the mass of the graphite sample is the gram capacity of the graphite material.

[0109] In some embodiments, the gram capacity of the graphite is 345 mAh / g, 346 mAh / g, 347 mAh / g, 348 mAh / g, 349 mAh / g, 350 mAh / g, 351 mAh / g, 352 mAh / g, 353 mAh / g, 354 mAh / g, 355 mAh / g, or any range therebetween.

[0110] During the charge and discharge process, the graphite material with a gram capacity within the above range will not have a significant lattice expansion due to the high graphitization of the graphite material; nor will it be difficult to compact due to the low graphitization of the graphite material, so that a higher cold pressing pressure is required to achieve the required compaction density of the pole piece, which will cause the graphite material to break during the cold pressing process and generate new interfaces during the cycle process to consume too much active lithium. The graphite material with a gram capacity within the above range can comprehensively improve the cycle life of the secondary battery.

[0111] In some embodiments, the graphite powder compaction density under a pressure of 49000N is less than or equal to 1.85g / cm 3 , optional 1.75g / cm 3 -1.84g / cm 3 .

[0112] In this article, the term "powder compaction density" refers to the mass of powder particles per unit volume under a certain pressure.

[0113] In this application, the powder compaction density of the active material under a pressure of 49000N can be tested by a method known in the art. As an example, referring to GB / T 24533-2009, 1g of graphite material powder is weighed and added to a bottom area of ​​1.327cm 2 The mold is pressurized to 4900 kg (equivalent to 49000 N), maintained for 30 seconds, then released and maintained for 10 seconds. The powder compaction density of the graphite material under a pressure of 49000 N is measured by an electronic pressure testing machine (such as UTM7305 electronic pressure testing machine).

[0114] In some embodiments, the powder compaction density of the graphite under a pressure of 49000N may be 1.69 g / cm 3 , 1.72g / cm 3 , 1.75g / cm 3 , 1.78g / cm 3 , 1.82g / cm 3 , 1.85g / cm 3 Or any range of values ​​in between.

[0115] Graphite materials with a powder compaction density within the above range can easily maintain high particle integrity during the cold pressing process, which helps to improve the cycle life of secondary batteries.

[0116] In some embodiments, the graphite particle body includes an internal region and a surface region at least partially surrounding the internal region, wherein the surface region refers to a region extending 30 nm from the surface of the particle body to the interior of the particle, and the surface region includes a disordered layer.

[0117] Figure 4 2 is a schematic diagram of a cross-sectional image of a particle of the graphite material 200 of the present application. Figure 4 As shown, the region extending 30 nm inward from the particle body surface of the graphite material 200 is the surface region 201, the region inside the surface region 201 is the internal region 202, and the surface region 201 includes a disordered layer.

[0118] The disordered layer can be obtained through transmission electron microscopy (TEM) testing. A thin slice of about 20 to 50 nm thickness is cut from the middle of the graphite material particle body by focused ion beam (FIB), and then the thin slice is tested by TEM. It can be observed that the surface area includes a layer of disordered layer whose transmission electron microscope morphology, lattice fringes, and electron diffraction patterns are different from those of the inner area. The electron diffraction pattern at the disordered layer is halo-shaped.

[0119] In some embodiments, the disordered layer has a thickness of 1 nm to 20 nm.

[0120] In the present application, the thickness of the disordered layer can be tested by methods known in the art. As an example, it can be obtained by transmission electron microscopy (TEM) testing. A thin slice with a thickness of about 20 to 50 nm is cut from the middle of the graphite material particle body by a focused ion beam (FIB), and then the thin slice is subjected to a TEM test to obtain an original TEM test image. The original image obtained by the above TEM test is opened in the Digital Micrograph software, and the disordered layer is identified by diffraction fringes or lattice spacing, and its thickness is measured. Normally, the disordered layer has no diffraction fringes, and the lattice spacing is larger than that of the ordered layer.

[0121] In some embodiments, the thickness of the disordered layer is 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, or any range therebetween.

[0122] The disordered layer mainly includes amorphous carbon. The carbon atoms in the amorphous carbon structure have no regular arrangement, which makes the interaction between its molecules more complex, resulting in higher strength and hardness than the graphite crystals in the internal area, which reduces the probability of surface damage of graphite particles due to friction between particles and between particles and stirring tanks during slurry preparation, reduces the risk of graphite material particles cracking and exposing new interfaces during the cold pressing of the pole piece, and allows the graphite material to maintain higher particle integrity during the manufacturing process. Graphite materials with high particle integrity have fewer surface defects and a good interface with the electrolyte, which can effectively reduce the side reactions between the negative electrode and the electrolyte, reduce the loss of active lithium, and are beneficial to the improvement of battery storage stability and cycle stability. At the same time, the disordered layer on the graphite material also helps to improve the infiltration of the electrolyte and the negative electrode, and improve the battery kinetic performance.

[0123] Different from the disordered layer coated on the surface of the graphite material in the prior art, the disordered layer of the graphite material provided in the embodiment of the present application is located in the particle body of the graphite material, which is derived from the same raw material as the graphite material and is not prepared by post-processing. Therefore, compared with the graphite material obtained by surface coating treatment to obtain the disordered layer, the graphite material has better material consistency, so that the battery exhibits a longer cycle life, and achieves a balance between battery kinetic performance and cycle stability and storage stability, and is particularly suitable for energy storage batteries with extremely high requirements for cycle life and storage life.

[0124] In some embodiments, the graphite includes both primary particles and secondary particles; optionally, based on the total number of the primary particles and the secondary particles, the number of the secondary particles accounts for less than or equal to 50%.

[0125] As used herein, the term "primary particles" refers to particles in a non-agglomerated state.

[0126] As used herein, the term "secondary particles" refers to particles in an agglomerated state formed by the aggregation of two or more primary particles.

[0127] Primary particles and secondary particles can be distinguished by observing the particle cross-section of the graphite material using a scanning electron microscope (SEM). In the present application, the proportion of the number of secondary particles in the graphite material can be tested by methods known in the art. As an example, a cross-section polisher (e.g., IB-09010 CP argon ion cross-section polisher of JEOL, Japan) can be used to prepare the cross-section of the negative electrode sheet; then, referring to JY / T010-1996, a scanning electron microscope (e.g., Sigma 300 scanning electron microscope of ZEISS, Germany) is used to scan the cross-section of the negative electrode sheet, and multiple test areas are randomly selected in the test sample, and images of multiple test areas are obtained using a scanning electron microscope, and the number of graphite materials with secondary particle morphology in each image is counted. The ratio of the total number of graphite material particles, and the average value of multiple statistical results is the number of secondary particles in the graphite material.

[0128] In some embodiments, the graphite includes both primary particles and secondary particles, and the number of the secondary particles accounts for 50%, 40%, 30%, 20%, 10% or any range therebetween based on the total number of the primary particles and the secondary particles.

[0129] Graphite materials with a low percentage of secondary particles are conducive to maintaining the particle integrity of graphite materials during battery preparation, reducing the generation of new interfaces, reducing the consumption of active lithium during the cycle, and further improving the cycle stability of secondary batteries. At the same time, a certain number of secondary particles can reduce the expansion of the negative electrode while taking into account the dynamic performance of the secondary battery, so that the battery cell has a dynamic window for the entire life cycle, and will not cause lithium precipitation due to uneven current distribution, causing a sharp decline in battery capacity and a sharp deterioration in battery life, thereby comprehensively improving the cycle stability of the battery.

[0130] In some embodiments, the graphite has a degree of graphitization of 92.0% to 94.0%.

[0131] As used herein, the term "degree of graphitization" refers to an index measuring the degree to which carbon atoms form a close-packed hexagonal graphite crystal structure.

[0132] In the present application, the graphitization degree of the graphite material can be tested by methods known in the art. As an example, high-purity silicon powder (purity ≥ 99.99%) is used as an internal standard for calibration, and the mixture is mixed according to a weight ratio of graphite material: silicon = 5:1, ground evenly, and pressed into a sheet for sample preparation. An X-ray diffractometer (such as Bruker D8 Discover) is used for testing, and JIS K0131-1996 and JB / T 4220-2011 are referred to to obtain the average interlayer spacing d002 of the (002) crystal plane in the crystal structure of the graphite material, and then the graphitization degree is calculated according to the formula g = (0.344-d002) / (0.344-0.3354) × 100%. In the above formula, d002 is the average interlayer spacing of the (002) crystal plane in the crystal structure of the graphite material expressed in nanometers (nm).

[0133] In some embodiments, the graphite has a degree of graphitization of 92%, 92.2%, 92.4%, 92.6%, 92.8%, 93%, 93.2%, 93.4%, 93.6%, 93.8%, 94%, or any range therebetween.

[0134] The graphite material having a degree of graphitization within the above range can achieve both cycle stability and high capacity.

[0135] In some embodiments, the graphite material I D / I G is 0.05-0.10, among which I D / I G is the ratio of the D peak intensity to the G peak intensity obtained from the Raman spectrum, I D Indicates that the Raman spectrum is at 1350±100cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±100cm -1 The G peak intensity at .

[0136] In this application, the graphite material I D / I G Any known mode of Raman spectroscopy can be used for testing. As an example, referring to GB / T 40219-2021, an InVia Qontor (Reflex) Raman spectrometer is used for testing; a solid laser with a wavelength of 523nm is used as the light source, 100 points are sampled in an area of ​​100μm×100μm, and I D / I G The median value of I of graphite material D / I G , the median is the collected I arranged in order of size D / I G The number in the middle of the data.

[0137] In some embodiments, the graphite material I D / I G It is 0.05, 0.06, 0.07, 0.08, 0.09, 0.10 or any numerical range therebetween.

[0138] Graphite Materials I D / I G It can be used to characterize the surface disorder of graphite materials. Different from the active material with a disordered layer coated on the surface of the graphite particle body, the graphite material provided in the embodiment of the present application has a disordered layer on the surface and has a lower surface disorder. The disordered layer in the active material with a disordered layer coated on the surface of the graphite particle body is usually derived from the coated organic carbon, so that the disordered layer after carbonization has a high surface disorder; while the disordered layer structure in the surface area of ​​the graphite material provided in the embodiment of the present application and the other parts of the graphite material are derived from the same precursor, and the disordered layer has a high uniformity and an extremely thin thickness, so that it can have a lower surface disorder. On the one hand, this enables the graphite material to take advantage of the disordered layer and improve the kinetic performance of the battery, and will not cause too many side reactions due to the excessive disorder of the surface layer of the material, and can take into account the cycle stability of the battery while improving the kinetic performance of the battery.

[0139] The present application has no particular restrictions on the type of secondary battery. For example, the secondary battery can be a lithium-ion battery, etc. In general, a secondary battery includes a positive electrode plate, a negative electrode plate, and an electrolyte, etc. During the charge and discharge process of the secondary battery, active ions are embedded and removed back and forth between the positive electrode plate and the negative electrode plate, and the electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate. The present application has no particular restrictions on the type of the electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (ie, an electrolyte). Secondary batteries using electrolytes and some secondary batteries using solid electrolytes may also include a separator, which is arranged between the positive electrode plate and the negative electrode plate to play an isolation role.

[0140] The present application also provides a method for preparing a graphite material, comprising the following steps: providing raw materials; processing the raw materials to obtain an intermediate product; graphitizing the intermediate product to obtain a graphite material; the particle body of the graphite material includes an internal region and a surface region that at least partially surrounds the internal region, the surface region refers to a region extending 30 nm from the surface of the particle body of the graphite material to the interior of the particle, and the surface region includes a disordered layer.

[0141] Herein, the term "graphitization treatment" refers to the heat treatment process of carbon materials, which is the process in which the carbon materials transform from a two-dimensional carbon network structure to a three-dimensional ordered structure through "microcrystal" growth under high temperature.

[0142] In some embodiments, the maximum power of the graphitization process is 70%-90% of the rated power of the graphitization process equipment.

[0143] In some embodiments, the maximum power of the graphitization treatment can be selected as 70%, 75%, 80%, 85%, 90% or any numerical range therebetween of the rated power of the graphitization treatment equipment. It is understood that the graphitization treatment device refers to any device capable of performing graphitization treatment, including but not limited to Acheson furnace, box furnace, inner series furnace, continuous graphitization, electric calcining furnace, medium frequency furnace, tubular furnace and other devices. Among them, the rated power of graphitization treatment equipment produced by different manufacturers may be different, and can be selected according to actual conditions. The maximum power of the graphitization treatment used in this application needs to be lower than the rated power of the graphitization treatment device to achieve uniformity of the thermal field during the graphitization treatment process.

[0144] The maximum power of the graphitization treatment used in this application needs to be lower than the rated power of the graphitization treatment equipment to achieve uniformity of the thermal field during the graphitization treatment process.

[0145] In some embodiments, the graphitization treatment equipment is an inner series furnace, and the rated power of the inner series furnace is 25000-32000 W. The graphitization treatment time can be 10h-30h, and can be optionally 15h-25h.

[0146] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the rated power of the Acheson furnace is 28000-30000 W. The graphitization treatment time can be 30h-50h, and can be optionally 40h-50h.

[0147] In some embodiments, the maximum power of the graphitization process is 22000W-25000W.

[0148] In some embodiments, the maximum power of the graphitization process may be 22000 W, 22500 W, 23000 W, 23500 W, 24000 W, 25000 W, or any range therebetween.

[0149] By controlling the maximum power of the graphitization treatment, the degree of graphitization of the graphite material during the heat treatment process can be effectively controlled. While the internal area of ​​the graphite material particles is highly graphitized, a uniform disordered layer is formed on the surface of the body, which is beneficial to improving the cycle stability of the secondary battery.

[0150] In some embodiments, the temperature of the graphitization treatment is 2600°C to 3000°C.

[0151] In some embodiments, the temperature of the graphitization treatment is 2600° C., 2700° C., 2800° C., 2900° C., 3000° C., or any range therebetween.

[0152] The appropriate graphitization treatment temperature and the appropriate graphitization treatment time are not likely to cause excessive rearrangement of the precursor, resulting in a high specific surface area of ​​the graphite material after graphitization and deterioration of high-temperature performance; it can also effectively improve the graphitization degree of the graphite material, thereby facilitating the simultaneous improvement of the high-temperature storage and cycle life of the secondary battery.

[0153] In some embodiments, the feedstock includes at least one of petroleum coke, needle coke, and asphalt coke, and needle coke may be selected.

[0154] As used herein, the term "petroleum coke" refers to coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt.

[0155] As used herein, the term "needle coke" refers to coal tar pitch or petroleum pitch, which, after undergoing liquid phase carbonization to generate an anisotropic mesophase, can generate coke with a needle-like texture after undergoing processes such as high-temperature carbonization.

[0156] As used herein, the term "pitch coke" refers to a solid material produced by carbonizing coal tar pitch at high temperatures.

[0157] Among them, needle coke has a series of advantages such as low thermal expansion coefficient, low porosity, low sulfur, low ash, low metal content, high conductivity and easy graphitization, etc. The graphite material after graphitization can reach a high ultimate compaction density and has a low cyclic expansion rate.

[0158] In some embodiments, based on the total volume of the raw material structure, the volume proportion of the fiber-type structure in the raw material is greater than or equal to 55%, and can be optionally 58%-70%.

[0159] In this article, "fibrous structure" is also called streamlined structure, which refers to the structure of the raw material with obvious fibrous texture observed under a microscope.

[0160] Generally, according to the morphological characteristics and isochromatic zone size of the raw material under a polarizing microscope, its microstructure can be divided into mosaic type, regional type and fiber type. Generally, isochromatic zone microstructure with a size of not less than 30μm is judged as mosaic type; isochromatic zone microstructure with a size greater than 30μm is judged as regional type, and anisotropic strip-shaped isochromatic zone is judged as fiber type structure.

[0161] In this application, the volume proportion of the fiber structure in the raw material can be tested by methods known in the art. As an example, take the raw material according to GB 1997-89, mix the raw material crushed to 1mm, shrink it to 40g~50g, use a square hole sieve to take 0.07mm~1.0mm grade sample 4g~5g for film making; prepare powder coke and block coke light film according to MT 116.1-86, the diameter of the powder coke light film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; place the sample on a slide with glue, flatten it, and then place it on the stage to focus, calibrate the microscope and adjust the polarizer and analyzer to make them orthogonal. Insert the azurite inspection plate (1λ) to make the field of view present the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3~0.5mm and the line spacing is generally 0.5~0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the fiber-type structure optical organization by the total number of statistical testing points as the volume proportion of the fiber-type structure in the raw material.

[0162] In some embodiments, based on the total volume of the raw material structure, the volume proportion of the fibrous structure in the raw material can be selected to be 55%, 58%, 60%, 65%, 70% or any range of values ​​therebetween.

[0163] Raw materials with more fiber-type structures are conducive to improving the compaction density and gram capacity of graphite materials, so that the graphite materials retain a high degree of integrity during the compaction process, and the battery has a high cycle life and good energy density; but too high a proportion of fiber-type structures will increase the cost and expansion rate of graphite materials and deteriorate dynamic performance. Raw materials with a volume proportion of fiber-type structures within the above range have both low costs and good gram capacity of graphite, and the battery cell has a full life cycle kinetic window, thereby comprehensively improving the long-term cycle life and electrochemical performance of the battery.

[0164] In some embodiments, the maximum gram capacity that can be achieved by the feedstock is greater than the gram capacity of the graphite material.

[0165] By using high-grade raw materials and controlling the degree of graphitization so that the maximum gram capacity that the raw materials can achieve is not fully utilized, a graphite material including a disordered layer in the surface area is obtained, thereby achieving a balance between battery cycle life and kinetic performance.

[0166] In some embodiments, the processing of raw materials specifically includes: crushing, shaping and grading the raw materials to obtain a first precursor; granulating the first precursor to obtain a second precursor; and low-temperature carbonizing a mixture of the first precursor and the second precursor to obtain the intermediate product.

[0167] Crushing is the process of reducing the particle size of raw materials. The raw materials can be crushed by any mechanical device such as crusher, mechanical mill, etc.

[0168] Shaping and classification is the process of adjusting the particle size distribution of the raw material to obtain a first precursor that meets the particle size requirements. The particle size and particle size distribution of the first precursor can be controlled by adjusting the classification frequency and air intake volume.

[0169] It can be understood that low-temperature carbonization of the first precursor and the second precursor to obtain the intermediate product includes both low-temperature carbonization of a mixture of the first precursor and the second precursor to obtain the intermediate product and low-temperature carbonization of the first precursor and the second precursor separately to obtain the first intermediate product and the second intermediate product respectively.

[0170] In some embodiments, the Dv50 particle size of the first precursor is 6.5 μm to 10.0 μm.

[0171] In some embodiments, the Dv50 particle size of the first precursor is 6.5 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, or any range therebetween.

[0172] In some embodiments, the particle size distribution of the first precursor (Dv90-Dv10) / Dv50 is 1.05-1.75.

[0173] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first precursor is 1.05, 1.15, 1.25, 1.35, 1.45, 1.55, 1.65, 1.75 or any range therebetween.

[0174] In some embodiments, the tap density of the first precursor is 0.5 g / cm 3 ~0.7g / cm 3 .

[0175] As used herein, the term "tapped density" refers to the mass per unit volume of powder in a container measured after being tapped under specified conditions.

[0176] In the present application, the tap density of the first precursor can be tested by a method known in the art. As an example, GB / T 5162-2006 can be referred to and a powder tap density tester can be used for measurement. The test instrument can be Dandong Better BT-301, and the test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder 25mL.

[0177] In some embodiments, the tap density of the first precursor is 0.5 g / cm 3 , 0.55g / cm 3, 0.6g / cm 3 , 0.65g / cm 3 , 0.7g / cm 3 Or any range of values ​​in between.

[0178] In some embodiments, the Dv50 particle size of the second precursor is 11.0 μm to 14.0 μm.

[0179] In some embodiments, the Dv50 particle size of the second precursor is 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, or any range therebetween.

[0180] The second precursor is obtained by granulating the first precursor, and therefore, the second precursor mainly forms secondary particles in the graphite material.

[0181] Controlling the particle sizes of the first precursor and the second precursor helps to regulate the particle size and particle size distribution of the graphite material and improve the cycle stability of the battery.

[0182] In some embodiments, the crushing, shaping and grading of the raw materials to obtain the first precursor includes: crushing, shaping and grading the raw materials to obtain secondary raw materials; removing fine powder accounting for 10%-35% of the total mass of the secondary raw materials to obtain the first precursor; the Dv50 of the fine powder is 3μm-7μm, and Dv99 is less than or equal to 30μm.

[0183] In some embodiments, the particle size distribution of the fine powder (Dv90-Dv10) / Dv50 is greater than 1.50.

[0184] In some embodiments, the temperature of low temperature carbonization is 900° C.-1300° C., and the time of low temperature carbonization is 24 h-240 h.

[0185] In some embodiments, the temperature of the low temperature carbonization may be selected to be 900° C., 1000° C., 1100° C., 1200° C., 1300° C., or any range therebetween.

[0186] In some embodiments, the low-temperature carbonization time may be 24 h, 50 h, 75 h, 100 h, 150 h, 200 h, 240 h, or any range therebetween.

[0187] [Negative electrode]

[0188] In some embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0189] like Figures 1 to 3 As shown, the negative electrode film layer 102 further includes a middle region 1023 located between the first region 1021 of the negative electrode film layer and the second region 1022 of the negative electrode film layer and having a thickness of 0.4H (H represents the thickness of the negative electrode film layer 102).

[0190] In some embodiments, the intermediate region includes the first adhesive and / or the second adhesive. Figure 2 As shown, the middle region 1023 may be the same as the first region 1021 in composition, whereby the distribution area of ​​the first binder in the thickness direction of the negative electrode film layer 102 is within the thickness range from the second surface 102b of the negative electrode film layer to 0.7H; or Figure 3 As shown, the middle region 1023 may be the same as the second region 1022 in composition, whereby the distribution area of ​​the second binder in the thickness direction of the negative electrode film layer 102 is within the thickness range from the first surface 102a of the negative electrode film layer to 0.7H; or Figure 1 As shown, the middle region 1023 includes both the first adhesive and the second adhesive. At this time, the middle region 1023 includes both the layer structure having the first adhesive and the layer structure having the second adhesive. The two-layer structure may also have a layer interface.

[0191] In some embodiments, the negative electrode film layer may further include other negative electrode active materials in addition to the above-mentioned active materials. In some embodiments, the other negative electrode active materials include but are not limited to one or more of conventional natural graphite, other artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material.

[0192] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.

[0193] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0194] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0195] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the present application also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode collector and the negative electrode film layer and disposed on the surface of the negative electrode collector; in some embodiments, the negative electrode plate described in the present application also includes a protective layer covering the surface of the negative electrode film layer.

[0196] [Positive electrode]

[0197] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0198] The positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0199] The positive electrode film layer generally includes a positive electrode active material, an optional binder, and an optional conductive agent. The positive electrode film layer is generally formed by coating a positive electrode slurry on the positive electrode current collector and then drying and cold pressing. The positive electrode slurry is generally formed by dispersing a positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring evenly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto. As an example, the binder for the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin. As an example, the conductive agent for the positive electrode film layer includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0200] The positive electrode active material can be a positive electrode active material for secondary batteries well-known in the art.

[0201] When the secondary battery of the present application is a lithium-ion battery, the positive electrode active material may include, but is not limited to, one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds. Examples of the lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the lithium-containing phosphates may include, but are not limited to, lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their respective modified compounds.

[0202] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium-ion battery may include a lithium transition metal oxide and its modified compounds having the general formula Li a Ni b Co c M d O e A f One or more of them. 0.8 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A is selected from one or more of N, F, S, and Cl.

[0203] In some embodiments, as examples, the positive electrode active material for a lithium ion battery may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 One or more of O2, LiFePO4 and LiMnPO4.

[0204] In the present application, the modified compound of each positive electrode active material mentioned above may be a compound obtained by doping and / or surface coating the positive electrode active material.

[0205] [Electrolytes]

[0206] In some embodiments, the electrolyte is an electrolyte solution, and the electrolyte solution includes an electrolyte salt and a solvent.

[0207] The type of the electrolyte salt is not particularly limited and can be selected according to actual needs.

[0208] When the secondary battery of the present application is a lithium ion battery, as an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0209] The type of the solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) One or more.

[0210] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high temperature performance of the secondary battery, and additives that improve the low temperature power performance of the secondary battery.

[0211] [Isolation film]

[0212] The present application has no particular limitation on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.

[0213] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.

[0214] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly by a winding process or a lamination process.

[0215] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0216] In some embodiments, the outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0217] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 5 The secondary battery 5 is a square structure as an example.

[0218] In some embodiments, Figure 6 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.

[0219] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the secondary battery is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0220] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.

[0221] Figure 7 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 7 As shown, in the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0222] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0223] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0224] Figure 8 and Fig. 9 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 8 and Fig. 9As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0225] The present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0226] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0227] Fig.10 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.

[0228] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0229] Example

[0230] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0231] In the following embodiments and comparative examples, the graphite material used can be purchased commercially or prepared by the following method of the present application.

[0232] Example 1

[0233] (1) Preparation of graphite:

[0234] The needle coke with a fiber structure of 63.7% was crushed; the crushed material was shaped to remove fine powder to obtain the first precursor. Some fine powder was removed from the first precursor, and the mass of the removed fine powder accounted for 21% of the total mass of the crushed material. The Dv50 of the fine powder was 3-7μm and Dv99 was less than or equal to 30μm. The particle size distribution of the fine powder (Dv90-Dv10) / Dv50 was greater than 1.6. Among them, the Dv50 particle size of the first precursor was 9.0μm, the particle size distribution (Dv90-Dv10) / Dv50 was 1.35, and the tap density of the first precursor was 0.65g / cm 3 .

[0235] The first precursor is granulated and shaped in a reaction kettle to obtain a second precursor with a particle size Dv50 of 14.1 μm;

[0236] The first precursor and the second precursor were placed in a kiln for carbonization at a temperature of 1100°C and a carbonization time of 24 hours to obtain a first intermediate product and a second intermediate product. The tap density of the first intermediate product was 0.98 g / cm 3 The tap density of the second intermediate product is 0.91 g / cm 3 ;

[0237] The first intermediate product and the second intermediate product are respectively placed in an inner series furnace for graphitization treatment at a temperature of 2800°C. The rated power of the inner series furnace is 28000W, the maximum power of the graphitization treatment is 22400W, and the constant power duration of the maximum power is maintained for 24 hours to obtain primary particles and secondary particles respectively.

[0238] The primary particles and the secondary particles are mixed evenly in a mass ratio of 1:1, and the final graphite material is obtained after sieving.

[0239] The thickness of the disordered layer of the graphite material is 11.3 nm. D / I G The interlayer spacing d1 of the disordered layer is 0.3368 nm, the interlayer spacing d2 of the inner region is 0.3361 nm, the particle size distribution (Dv90-Dv10) / Dv50 is 1.28, and the specific surface area is 1.65 m 2 / g, the volume distribution particle size Dv50 is 10.2μm, and the powder compaction density under a pressure of 49000N is 1.81g / cm 3 , the gram capacity is 350.4mAh / g.

[0240] (2) Preparation of negative electrode sheet

[0241] The graphite negative electrode active material prepared above, conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and linear binder polyacrylic acid were fully stirred and mixed in a proper amount of solvent deionized water at a mass ratio of 96.3:1:1.2:1.5 to form a first slurry.

[0242] The graphite negative electrode active material prepared above, conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and point binder styrene-butadiene rubber were fully stirred and mixed in a proper amount of solvent deionized water at a mass ratio of 96.8:1:1.2:1.0 to form a second slurry.

[0243] The second slurry and the first slurry are extruded simultaneously through a double-chamber coating device. The first slurry is coated on the negative electrode current collector copper foil, and the second slurry is coated on the first slurry; after drying and cold pressing, the negative electrode sheet is obtained. The coating mass of the first slurry and the second slurry is the same, both 5.0 mg / cm 2 .

[0244] (3) Preparation of positive electrode sheet

[0245] The positive electrode active material lithium iron phosphate (LFP), the conductive agent Super P, and the binder polyvinylidene fluoride PVDF were mixed in a mass ratio of 97:1:2, and the solvent NMP was added. The system was stirred under the action of a vacuum mixer until it was uniform to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet was obtained after drying, cold pressing, and slitting. The compaction density of the positive electrode film layer is 2.50g / cm 3 , the surface density is 19.47mg / cm 2 .

[0246] (4) Preparation of electrolyte

[0247] In an argon atmosphere glove box with a water content of <10ppm, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L, and then vinylene carbonate (VC) is added, and the content of VC is 2% of the total mass of the electrolyte.

[0248] (5) Preparation of isolation membrane

[0249] Polypropylene film is used as the isolation film.

[0250] (6) Preparation of lithium-ion batteries

[0251] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0252] In Examples 2-8, the type of binder in the first slurry and / or the second slurry and / or the mass content of the binder in the first slurry or the second slurry are adjusted; see Table 1 for details.

[0253] Table 1

[0254]

[0255] The preparation methods of Comparative Example 1 are basically the same as those of Example 1, except that a dot-shaped binder is used in both the first region and the second region of the negative electrode film layer.

[0256] The preparation method of Comparative Example 2 is basically the same as that of Example 1, except that a linear binder is used in both the first region and the second region of the negative electrode film layer.

[0257] The preparation method of Comparative Example 3 is substantially the same as that of Example 1, except that the second slurry is coated on the negative electrode current collector copper foil, and the first slurry is coated on the second slurry.

[0258] Performance Testing

[0259] (1) Electrode rebound rate and cycle expansion rate

[0260] Rebound rate of the electrode: The thickness of the negative electrode after cold pressing is L0. The thickness of the negative electrode after cold pressing is tested at 25°C and 10% humidity for 24 hours, and the thickness of the negative electrode is L1. The rebound rate of the electrode V0 = (L1-L0) / L0;

[0261] Cyclic expansion rate of the electrode plate: The batteries of the above-mentioned embodiments and comparative examples are charged at a constant current of 1C to a voltage of 3.65V, and then charged at a constant voltage of 3.65V to a current ≤ 0.05C. Then the batteries are discharged at a constant current of 1C to a voltage of 2.5V. This is one charge and discharge process. After repeating the charge and discharge cycle for 100 times, the thickness L2 of the negative electrode plate is tested. The cyclic expansion rate of the electrode plate V2 = (L2-L0) / L0.

[0262] (2) Cohesive strength test

[0263] Cut the negative electrode into strips with a length of 20 cm and a width of 20 mm, evenly stick 3M tape on the surface of the strip (make sure the surface is smooth and wrinkle-free after sticking), keep a small piece of copper foil tape on the paper, roll the tape back and forth 4 times with a roller, clamp the white paper on the tensile testing machine fixture, start the tensile testing machine test, so that the single-sided tape sticking to the negative electrode active material layer of the strip is separated from the strip, and the cohesive force value is obtained after the test is completed. The force divided by the width of the test strip (20 mm) is used as the cohesive strength (N / m) between particles in the negative electrode film layer.

[0264] (3) Cyclic performance test

[0265] At 60°C, the batteries of the above embodiments and comparative examples were charged at a constant current of 1C to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current ≤ 0.05C, and then discharged at a constant current of 1C to a voltage of 2.5V. This was a charge and discharge process, and the discharge capacity C1 of the first cycle was recorded. The charge and discharge cycles were repeated until the battery capacity decayed to 80% of the initial capacity C1, and the test was stopped, and the number of cycle tests was recorded.

[0266] (4) Dynamic performance test

[0267] At 25°C, the secondary battery was charged to 3.65V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage, and after standing for 5 minutes, the secondary battery was discharged to 2.50V at a constant current of 0.33C, and its actual capacity was recorded as C0.

[0268] Then the secondary battery is charged with a constant current of 1.0 C0, 1.3 C0, 1.5 C0, 1.8 C0, 2.0 C0, 2.3 C0, 2.5 C0, 3.0 C0, to a negative electrode cut-off potential of 3.5V or 0V (whichever is reached first), and it needs to be discharged to 2.5V at 1C0 after each charging is completed. The negative electrode potential corresponding to charging to 10%, 20%, 30%, ..., 80% SOC (State of Charge) at different charging rates is recorded, and the charging rate-negative electrode potential curve under different SOC states is drawn. After linear fitting, the charging rate corresponding to the negative electrode potential of 0V under different SOC states is obtained. The charging rate is the charging window under the SOC state, which is recorded as C10% SOC, C20% SOC, C30% SOC, C40% SOC, C50% SOC, C60% SOC, C70% SOC, C80% SOC, according to the formula (60 / C10% SOC+60 / C20% SOC+60 / C30% SOC+60 / C40% SOC+60 / C50% SOC+60 / C60% SOC+60 / C70% SOC+60 / C80% SOC)×10%, the charging time T of the secondary battery from 10% SOC to 80% SOC (under the premise that the secondary battery does not precipitate lithium) is calculated in min. The shorter the charging time, the better the kinetic performance of the secondary battery.

[0269] Test Results

[0270] The test results are shown in Tables 2 and 3. As can be seen from Table 2, the secondary battery includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, the negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is recorded as H, the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the first area of ​​the negative electrode film layer, and the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the second area of ​​the negative electrode film layer. The first area includes a first binder, which is a linear binder; the second area includes a second binder, which is a point-shaped binder, which is beneficial to reducing the cold pressure rebound rate and cycle expansion rate of the plate and improving the cycle stability of the battery.

[0271] Table 2

[0272] Serial number The rebound rate of the pole piece V0 Cyclic expansion rate of the pole piece V2 Cycle number / circle Example 1 5.9% 29.5% 1921 Example 2 5.3% 29.9% 1992 Comparative Example 1 10.4% 33.1% 1752 Comparative Example 2 9.5% 32.2% 1787 Comparative Example 3 9.1% 32.6% 1781

[0273] It can be seen from Table 3 that when the mass proportion of the first binder in the first region is 1.0% to 2.5% and / or the mass proportion of the second binder in the second region is 0.6% to 1.2%, the battery has both good cycle stability and kinetic performance.

[0274] Table 3

[0275]

[0276] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A secondary battery, characterized in that: The invention comprises a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is recorded as H, the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the first area of ​​the negative electrode film layer, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the second area of ​​the negative electrode film layer, the first area comprises a first binder, and the first binder is a linear binder; the second area comprises a second binder, and the second binder is a point binder.

2. The secondary battery according to claim 1, characterized in that: The weight average molecular weight of the first binder is greater than the weight average molecular weight of the second binder.

3. The secondary battery according to claim 1 or 2, characterized in that: The mass proportion of the first binder in the first region is greater than the mass proportion of the second binder in the second region; the mass proportion of the first binder in the first region refers to the mass percentage of the first binder based on the total mass of the negative electrode film layer in the first region; the mass proportion of the second binder in the second region refers to the mass percentage of the second binder based on the total mass of the negative electrode film layer in the second region.

4. The secondary battery according to any one of claims 1 to 3, characterized in that: The first adhesive includes an acrylic adhesive; and / or the second adhesive includes polystyrene butadiene copolymer.

5. The secondary battery according to claim 4, characterized in that: The acrylic adhesive includes at least one of polyacrylic acid, polymethacrylic acid, polymethyl acrylate, polyethyl methacrylate, polyhydroxyethyl methacrylate, polyhydroxyethyl acrylate, polyhydroxypropyl acrylate, polyhydroxypropyl methacrylate, polyhydroxyethyl acrylate, polypropyl methacrylate, polypropyl methacrylate, polyethyl acrylate, and polymethyl methacrylate.

6. The secondary battery according to any one of claims 1 to 5, characterized in that: The weight average molecular weight of the first binder is 500-1500, and can be 800-1000; the weight average molecular weight of the second binder is 100-200.

7. The secondary battery according to any one of claims 1 to 6, characterized in that: The mass proportion of the first binder in the first region is 1.0% to 3.0%, optionally 1.0% to 2.5%, and / or the mass proportion of the second binder in the second region is 0.6% to 1.5%, optionally 0.6% to 1.2%.

8. The secondary battery according to any one of claims 1 to 7, characterized in that: The negative electrode film layer satisfies at least one of the following conditions: (1) The compaction density of the negative electrode film layer is 1.55 g / cm 3 -1.68g / cm 3 ; (2) The negative electrode film layer includes a conductive agent, and based on the total mass of the negative electrode film layer, the mass proportion of the conductive agent is 0.4%-2.0%.

9. The secondary battery according to any one of claims 1 to 8, characterized in that: The first region and / or the second region comprises graphite, and the graphite satisfies at least one of the following conditions: (1) The specific surface area of ​​the graphite is 1.2 m 2 / g-1.8m 2 / g, optional 1.25m 2 / g-1.70m 2 / g; (2) The volume distribution particle size Dv50 of the graphite is 7.0 μm-14.0 μm, and can be optionally 9.0 μm-12.0 μm; (3) The particle size distribution of the graphite (Dv90-Dv10) / Dv50 is 1.10-1.60, and can be optionally 1.20-1.50; (4) The gram capacity of the graphite is 345 mAh / g-355 mAh / g, and can be optionally 347 mAh / g-353 mAh / g; (5) The graphite powder compaction density under a pressure of 49000N is less than or equal to 1.85g / cm 3 , optional 1.75g / cm 3 -1.84g / cm 3 ; (6) The graphite particle body includes an inner region and a surface region at least partially surrounding the inner region. The surface region refers to the region extending from the surface of the particle body to the inside of the particle by a distance of 30 nm, and the surface region includes a disordered layer; optionally, the thickness of the disordered layer is 1 nm- 20nm; (7) The graphite includes both primary particles and secondary particles; optionally, based on the primary particles and the The secondary particles account for less than or equal to 50% of the total number of secondary particles; (8) The graphitization degree of the graphite is 92.0%-94.0%; (9) I of the graphite material D / I G is 0.05-0.10, among which I D / I G is the ratio of the D peak intensity to the G peak intensity obtained from the Raman spectrum, I D Indicates that the Raman spectrum is at 1350±100cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±100cm -1 The G peak intensity at .

10. An electrical device comprising the secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Negative plate and lithium ion battery comprising same

    CN112103468A

  • Negative electrode for rechargeable lithium battery and rechargeable lithium battery including same

    CN114520315A

  • Negative active material, method for preparing same, secondary battery, and battery module, battery pack and device including secondary battery

    CN114730875A

  • High-rate long-cycle porous spherical carbon negative electrode material and preparation method thereof

    CN114772590A

  • Negative electrode material, preparation method thereof and lithium ion battery

    CN115377393A

Cited By

  • Secondary battery and electric device

    EP4811439A1